The Effect of Balanced Funds and Local Own-Source Revenue on Regional Expenditure and Economic Growth Before The COVID-19 Pandemic in Samarinda City - Kristin Wulansari; Della Olivia Caterina Kalangit; Suminto Suminto; Dyah Kusrihandayani (Journal Research of Social Science, Economics, and Management, 2022)
The aims of this study are to analyze the effect of balancing funds and local own-source revenue on regional expenditure and economic growth before the covid-19 pandemic in Samarinda City. The data used in this study is secondary data, which was obtained in 2014–2019. The analytical tool used is path analysis with IBM-SPSS Version 24. Research results showing that the Balancing Fund take effect direct and not significant to regional expanditure, strengthened score significance 0.356 > 0.05, with score influence direct of -0.318. Balancing Fund take effect direct and not significant to economic growth, strengthened score significance 0.127 > 0.05 with score influence direct of -0.390. Local own-source revenuehas an effect direct and significant to Regional Expenditure, strengthened score significance 0.031 < 0.05 with score influence direct of 1,126. Local own-source revenue has an effect direct and significant to Economic Growth, strengthened score significance 0.027 < 0.05 with score influence direct amounted to 1,879. Influential Regional expanditure direct and not significant to Economic Growth, strengthened score significance 0.106 > 0.05 with score influence direct of -0.728. Local Own-source revenue has no direct and insignificant effect on Economic Growth through Regional Expenditures with the effect of a score of 0.231. Balancing Fund has no direct and not significant to Economic Growth through Regional expenditure with score influence of -0.819.